FIRST OCCURRENCE OF CLOSE-TO-IDEAL KIRKIITE AT VULCANO (AEOLIAN ISLANDS, ITALY): CHEMICAL DATA AND SINGLE-CRYSTAL X-RAY STUDAY - Pinto D.; Garavelli A.; Vurro F.; Balić-Žunić T.; Makovicky E.; Garbarino C. (My University, 2006)
Samples of kirkiite from the high temperature fumaroles of La Fossa crater of Vulcano (Aeolian islands, Italy) were chemically and structurally investigated in this work. Associated minerals are vurroite, bismuthinite, galenobismutite, cannizzarite, lillianite, heyrovskýite, galena, and other less characterized Pb(Bi)-sulfochlorides. Electron-microprobe analyses gave the average chemical formula Pb10.00Bi3.01As3.01 (S18.47Se0.44Cl0.06) ∑=18.97, which is very close to the ideal composition of kirkiite, Pb10Bi3As3S19, and indeed significantly closer than the composition of the type specimen, Pb10.08Bi2.55Sb0.13 As2.91S19. Lattice parameters are: a = 8.700(2) Å, b = 26.237(6) Å, c = 8.774(3) Å, βB = 119.653(4)°, V = 1740.2(9)Å 3. A twinned structure was refined using single-crystal data (MoKα X-ray diffraction, CCD detector). The refinement converges to R = 0.074 for 1443 reflections with Fo > 4σ(Fo). The structure of the close-to-ideal kirkiite from Vulcano has been compared with the structure of the type specimen. The comparison reveals a variation in As-Bi substitution, with samples from Vulcano probably being close to the maximum possible Bi and the minimum As content for this structure type. This is reflected in more regular and symmetric coordination polyhedra than in the holotype, as well as in the overall regularity of the structure. The increased Bi:As ratio produces an elongation of the a and b lattice periods, and a shortening of the c period, and increases the frequency of twinning in kirkiite. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: CRYSTAL STRUCTURE; KIRKIITE; SULFOSALTS; TWINNING; VULCANO FUMAROLES